Acute Toxicity Evaluation of Phyllanthus niruri SNEDDS Formulation According to OECD 425 - Hikmah, Uzulul; Ramadani, Arba Pramundita; Canastie, Putri Julia; Ma'wa, Nurul Jannatul (EKSAKTA: Journal of Sciences and Data Analysis, 2026)
A self-nanoemulsifying drug delivery system (SNEDDS) is a preparation that can increase the solubility of poorly soluble compounds, including Phyllanthus niruri. However, increasing solubility and bioavailability carries the risk of increased toxicity. Previous research showed that SNEDDS of Phyllanthus niruri (SNPN) at a dose of 100 mg/kgBW has hepatoprotective activity through decreasing ALT and AST enzyme levels after administering paracetamol at a dose of 3 g/kgBW in rats. However, at a dose of 200 mg/kg, ALT and AST levels increased, indicating potential toxicity. This study aims to determine the LD50 and to conduct histopathological observations of the liver and kidneys following oral administration of SNPN, in accordance with OECD 425 guidelines. Dose determination follows the recommendations of the AOT 425 StatPgm software, which includes the limit test (2000 mg/kg BW) and the main test (175, 550, and 2000 mg/kg BW), with observations made over 14 days. Next, the animals were sacrificed and necropsied to collect the liver and kidney organs for histopathological observation. LD50 determination was performed using AOT 425 StatPgm, and the level of organ damage was assessed using histopathological scoring. The result showed that the LD₅₀ value of SNPN exceeded 2000 mg/kgBW, placing it in category 5 (mild toxicity). Histopathological tests showed varying severity of changes between doses, indicating a toxic effect of SNPNadministration on the microscopic structure of the target organs. In conclusion, SNPN administration has the potential to cause mild acute toxicity, as indicated by the LD50 results and histological changes in the liver and kidneys.